A randomized, placebo‐controlled study to evaluate safety and pharmacokinetics of inhaled ribavirin. Issue 9 (24th June 2022) - Couroux, Peter; Brkovic, Alexandre; Vittitow, Jason L.; Israel, Robert J.; Pamidi, Chinna; Patel, Jignesh; Barakat, Maxime
Abstract: Ribavirin is an inosine monophosphate dehydrogenase inhibitor. Studies suggest ribavirin aerosol could be a safe and efficacious treatment option in the fight against coronaviruses. However, current treatment is long (12–18 h per day, 3–7 days), limiting clinical utility. A reduction in treatment time would reduce treatment burden. We aimed to evaluate safety and pharmacokinetics (PK) of four, single‐dose regimens of ribavirin aerosol in healthy volunteers. Thirty‐two subjects were randomized, to four cohorts of aerosolized ribavirin (active) or placebo. Cohort 1 received 50 mg/ml ribavirin/placebo (10 ml total volume); cohort 2, 50 mg/ml ribavirin/placebo (20 ml total volume); cohort 3, 100 mg/ml ribavirin/placebo (10 ml total volume); and cohort 4, 100 mg/ml ribavirin/placebo (20 ml total volume). Intense safety monitoring and PK sampling took place on days 1, 2, 3, and 40. Subjects were (mean ± SD, active vs. placebo) aged 57 ± 4.5 vs. 60 ± 2.5 years; 83% vs. 88% were female; and 75% vs. 50% were Caucasian. Some 12.5% (3/24) and 25% (2/8) experienced at least one treatment‐emergent adverse event (TEAE) (two moderate; five mild) in the active and placebo groups, respectively. No clinically significant safety concerns were reported. Mean maximum observed concentration ( C max ) and area under the curve (AUC) values were higher in cohort 4, whereas cohorts 2 and 3 showed similar PK values. Ribavirin absorption reached C max within 2 h across cohorts. Four single‐dose regimens of ribavirin aerosol demonstrated systemic exposure with minimal systemic effects. Results support continued clinical development of ribavirin aerosol as a treatment option in patients with coronaviruses.